Using Software in a traffic noise barrier design for the southern side of Tishreen University - فوزي نرجس; شيبان سامية; محمود حبيب (Latakia University Journal -Engineering Sciences Series, 2022)
Traffic overcrowding is the main source of noise pollution in major cities, which causes severe health risks to humans. Noise barriers are the main tool for reducing traffic-related noise. In this study, field measurements were performed to calculate the levels of traffic noise in a section of the street overlooking the College of Education _ Tishreen University _ Lattakia, which is 11m far from the road axis, using an Audio and Acoustic Analyzer XL2-NTi, and to determine the amount of noise reaching the affected rooms inside the college, which overlooks the Street, the average results of the measurements in the three floors were (67.59 ± 0.9, 68.06 ± 0.76, 68.8 ± 1.6) dB, respectively, at two o’clock in the afternoon, which was considered peak hour, so these values exceed the permissible limits according to the Syrian standard specifications (55dB) for residential areas. Traffic density data on both directions of the road as well as spatial dimensions, elevations, weather conditions (temperature, humidity) and pavement type in the study area were employed in an engineering program used to predict and analyze noise levels associated with highways (FHWA TNM®, Traffic Noise Model) version 3.0. The noise simulations generated by the software were in agreement with field measurements and the difference between the results did not exceed 0.5dB. After verification, the program was used to evaluate the effectiveness of different models of noise barriers in reducing noise, where several barrier heights from 1m to 4m, and several types of barriers varies by the Noise Reduction Coefficient (NRC) were tested. The research showed the benefit of using traffic noise prediction programs and designing barriers before constructing noise-sensitive facilities. It is also necessary to take into account the aesthetic and economic aspect by employing local evergreen plants.